The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ob01855a
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in nickel-catalyzed carboboration of alkenes

Abstract: Alkenes represent one of the most useful building blocks for organic synthesis, owing to their abundance and versatile reactivity. Transition metal (Pd, Cu, Co, Ni, Fe, etc.) catalyzed difunctionalization of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…As for related Ni-catalyzed chain-walking reactions, we anticipated significant differences depending on the ligand employed. 8,9,24 As shown in entries 2− 5, this turned out to be the case. Intriguingly, however, ligands previously described to efficiently enable 1,1-difunctionalization 33 failed to provide significant amounts of 3a, whereas the utilization of electron-deficient olefin ligands provided the best results.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…As for related Ni-catalyzed chain-walking reactions, we anticipated significant differences depending on the ligand employed. 8,9,24 As shown in entries 2− 5, this turned out to be the case. Intriguingly, however, ligands previously described to efficiently enable 1,1-difunctionalization 33 failed to provide significant amounts of 3a, whereas the utilization of electron-deficient olefin ligands provided the best results.…”
mentioning
confidence: 85%
“…As expected, the solvent, temperature, nickel precatalyst, base, and concentration had a non-negligible impact on the reaction outcome (entries 6–10). As for related Ni-catalyzed chain-walking reactions, we anticipated significant differences depending on the ligand employed. ,, As shown in entries 2–5, this turned out to be the case. Intriguingly, however, ligands previously described to efficiently enable 1,1-difunctionalization failed to provide significant amounts of 3a , whereas the utilization of electron-deficient olefin ligands provided the best results. Tentatively, this observation suggests that the presence of the latter might facilitate a final sp 3 C–N bond reductive elimination en route to 3a .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, transition metal catalyzed 1,2-arylboration need to employ activated alkenes to increase the insertion rate before the direct reaction of aryl electrophiles such as aryl halides with boron nucleophiles. 14 In fact, unactivated alkenes are still challenging targets in 1,2-arylboration reactions. It is worth noting that Zhang et al demonstrated a Pd-catalyzed intramolecular cyclization of unactivated alkene to obtain indoline boronic esters up to 98% yield 15 .…”
Section: Synlett Lettermentioning
confidence: 99%
“…Chiral organoboron compounds occupy paramount significance as fundamental building blocks with a broad spectrum of applications in organic synthesis and medicinal chemistry, which is not only attributed to the low toxicity but also because the C–B bond can be utilized as a versatile handle to access virtually all functional groups for value-added products synthesis. , Transition-metal-catalyzed enantioselective borylation has emerged as the most practical method to construct this skeleton, mainly including cross-coupling and C–H borylation, as well as hydroborylation and carboborylation of unsaturated hydrocarbons. , For instance, the employment of catalytic M–B species as nucleophiles, such as Cu–B, Pt–B, and Ni–B species, can undergo the stereoselective migratory insertion toward the alkene to forge the C–B bond, and the resulting C–M species can then react with external electrophiles. Additionally, the Pd­(II)-catalyzed Wacker-type anticarboborylation of alkenes also represents an important strategy for the synthesis of chiral organoboron compounds as independently developed by Engle and coworkers and by the Chen and He group .…”
mentioning
confidence: 99%